2020
DOI: 10.1039/d0cc06313d
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY based realtime, reversible and targeted fluorescent probes for biothiol imaging in living cells

Abstract: Real-time live cell imaging and quantification of biothiols dynamics are important for understanding the pathophysiological process. However, it is still challenging in the design and synthesis of rational probes that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…As the product of C was known to react with biothiol in live cells and to produce E (BOD-OHS) with the fluorescence emission shifted from 673 to 548 nm (Scheme 4a). [15] As expected, we observed that cells were fluorescent (λ ex = 488 nm) under the illumination, but without illumination they were not.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…As the product of C was known to react with biothiol in live cells and to produce E (BOD-OHS) with the fluorescence emission shifted from 673 to 548 nm (Scheme 4a). [15] As expected, we observed that cells were fluorescent (λ ex = 488 nm) under the illumination, but without illumination they were not.…”
supporting
confidence: 83%
“…As we have reported before, formyl-BODIPY C can react with thiols via Michael addition (t 1/2 = 16 ms) to produce E (BOD-OHS). [15] We conducted several reactions to further confirm the proposed mechanism of the photorelease progress. First, A (BOD-dOH, 0.1 mmol) was illuminated to release C (BOD-OH) and D with good isolated yields for C and D, 75 % and 90 %, respectively (Scheme 3a).…”
mentioning
confidence: 87%
“…[60] More recently, another example bearing styryl substitution on position 3 reported successful access to mitochondria by inclusion of an end triphenylphosphonium group on the meso substituent (35). [81] It was observed that the absence of the mitochondrial targeting motif in the parent system led to accumulation in different organelles. Another probe (36), sharing some structural similarities with 35 was reported.…”
Section: Bodipysmentioning
confidence: 99%
“…Utilization of trifluoromethyl substitution on neutral BODIPY based architectures ( 33 and 34 ) resulted in subcellular accumulation within the mitochondria but also in the lysosomes [60] . More recently, another example bearing styryl substitution on position 3 reported successful access to mitochondria by inclusion of an end triphenylphosphonium group on the meso substituent ( 35 ) [81] . It was observed that the absence of the mitochondrial targeting motif in the parent system led to accumulation in different organelles.…”
Section: Bodipysmentioning
confidence: 99%
See 1 more Smart Citation